(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to compare the results of conventional and laparoscopic adrenalectomy in patients with adrenal masses greater than 6 cm.Material and Methods: Thirty-six patients with tumor size greater than 6 cm who underwent adrenalectomy between January 2011 and January 2018 were included in the study. Patients were divided into two groups as Group 1 conventional and Group 2 Laparoscopic surgery. The two groups were retrospectively compared in terms of age, sex, mass localization, mass size, duration of operation, amount of bleeding, duration of hospitalization, duration of onset of food intake, perioperative mortality, early period complications and re-admission to the hospital within 90 days. P0.05 was considered statistically significant.Results: There were 13 patients in Group 1 and 23 patients in Group 2. There was no statistically significant difference between the groups in terms of age, sex, tumor localization, tumor size, indications for operation, postoperative complications, perioperative mortality and readmission within 90 days. Duration of operation (min), amount of bleeding (ml), duration of oral intake (day) and duration of hospitalization (day) were higher in Group 1 and statistically significant.Conclusion: Laparoscopic adrenalectomy has demonstrated advantages in patients with a mass greater than 6 cm compared to conventional surgery, such as short operation duration, less blood loss, early onset of oral food intake and shorter hospital stay. It can be safely used in patients with a mass larger than 6 cm.